Optimal control of real and reactive power flow for improvements in voltage profiles and for real power loss minimization - Macasaet, Kalayaan M. (2004)
The project aims to minimize system fuel costs and real power losses and to optimize the reactive power flow for each bus in a large power system to enhance the performance of real power generation allocation for economic dispatch. The economic real scheduling was performed using the Lagrangian method and the reactive power was calculated using the gradient method. The impedance matrix was incorporated in the approach to the problem. Repeated alternate solutions of the real and reactive power was performed until the total production cost was minimized and within system constraints. The algorithm was simulated using the IEEE 30-bus text system. The parameters analyzed were the total system losses, total generation costs, and the real power generation of individual generators. Reactive power in each bus were also motivated. A steady state system was assumed and deregulation was not considered.